An Analysis of Students’ Difficulties in Understanding English Reading Comprehension on Narrative Text for Eighth Grade at SMP Ma’arif Miftahul Ulum Melirang - Nafa Saffanatut Tijani; Lailatul Masruroh (E-Link Journal, 2025)
This study examines the challenges faced by eighth-grade students at SMP Ma’arif Miftahul Ulum Melirang in comprehending English narrative texts, a crucial component of reading comprehension. The research addresses two main questions: what specific difficulties students face, and what factors contribute to these challenges. Using a descriptive qualitative method, the study involved 23 students through tests and questionnaires. The tests consisted of multiple-choice, short-answer, and true/false questions, while the questionnaire gathered students’ perceptions of their reading difficulties. The findings reveal that students struggle with four key aspects of reading comprehension: identifying main ideas, understanding vocabulary, making inferences, and recognizing detailed information. The most significant challenge was answering short-answer questions, which indicated a gap in understanding detailed content and vocabulary. Additionally, the study identified three primary factors contributing to these difficulties: the students’ backgrounds, including low motivation and fear of English; teaching techniques that were not well-aligned with students’ needs; and unsupportive learning environments. These findings highlight the need for improved teaching strategies and supportive environments to enhance students’ reading comprehension skills.